Wiji Thukul's Literary Practices as Literature Teaching Materials in Higher Education - Panji Kuncoro Hadi; Rosita Ambarwati; Bambang Eko Hari Cahyono (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to delineate Wiji Thukul's literary praxis as pedagogical content for literary education in tertiary institutions. Pierre Bourdieu's concept of cultural production theory is the theoretical framework employed to elucidate Wiji Thukul's literary practice and its applicability as instructional material in literature studies at universities. This research adopts a qualitative descriptive approach. The primary data for this investigation consists of various documents, including articles, journalistic notes, and investigative reports. Drawing from this corpus, the data collection method entails a literature review, while content analysis is the primary data analysis technique. The findings of this study underscore the contemporary relevance of Wiji Thukul's literary praxis, thereby advocating its integration as instructional material for literature studies in universities. This recommendation arises from the observation that current teaching materials for literature studies in higher education predominantly concentrate on literary works as objects of study.